The Relationship Between Geography Teacher Performance and Student Learning Outcomes Through the Use of the Deep Learning Model at SMAN 45 and SMAN 72, Kelapa Gading District, North Jakarta - Ihwan, Ihwan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the relationship between Geography teacher performance and student learning outcomes through the Deep Learning model approach at SMAN 45 and SMAN 72, Kelapa Gading District, North Jakarta. The teacher performance assessed includes aspects of learning planning, implementation, assessment, professionalism, communication, and utilization of technology and the development of 21st-century skills. The research method used is quantitative with a descriptive approach and correlational analysis. The population in this study were Geography Teachers and Students at SMAN 45 and SMAN 72 with a sample of 2 Geography teachers and 63 students in grade XI. Data were obtained through teacher performance questionnaires and documentation of student learning outcomes from three forms of assessment: UH 1, UTS, and UAS. The results of the analysis show that the performance of Geography teachers at SMAN 45 and SMAN 72, Kelapa Gading District, is generally in the good category, based on indicators that include learning planning, learning implementation, learning evaluation, and personality and social competencies, especially in encouraging deep learning through reflective, collaborative, and problem-solving-based methods.